The Battle of Surabaya November 1945 in Humaniter Law Perspective - Muhamad Idris; Esra Kriahanta Sembiring (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Battle of Surabaya in November 1945 which lasted for 3 weeks was the most intense battle during the Revolutionary Independence of the Republic of Indonesia in 1945 – 1949.  The Battle of Surabaya those involved from the Indonesian side are regular soldiers and fighters consisting of volunteers or militias who are members of several groups of fighters. These fighters considered that the arrival of British troops accompanied by the Netherland Indies Civil Administration/NICA army as an effort to take the Independence of the Republic of Indonesia which had been proclaimed on August 17, 1945. Therefore, They needed to defend Surabaya from the occupation by the Dutch and The Battle of Surabaya became an inspiration for all Indonesian people to maintain Indonesian independence. This paper will discuss how the distinction principles that distinguish between combatants and non-combatants and the concept of direct participation in the Battle of Surabaya in November 1945 and discuss whether the spontaneity of the people of Surabaya as levée en masse.